Improving Cardiac Reprogramming for Heart Regeneration in Translational Medicine - Liu Liu; Yijing Guo; Zhaokai Li; Zhong Wang (Cells, 2021)
Direct reprogramming of fibroblasts into CM-like cells has emerged as an attractive strategy to generate induced CMs (iCMs) in heart regeneration. However, low conversion rate, poor purity, and the lack of precise conversion of iCMs are still present as significant challenges. In this review, we summarize the recent development in understanding the molecular mechanisms of cardiac reprogramming with various strategies to achieve more efficient iCMs. reprogramming. Specifically, we focus on the identified critical roles of transcriptional regulation, epigenetic modification, signaling pathways from the cellular microenvironment, and cell cycling regulation in cardiac reprogramming. We also discuss the progress in delivery system optimization and cardiac reprogramming in human cells related to preclinical applications. We anticipate that this will translate cardiac reprogramming-based heart therapy into clinical applications. In addition to optimizing the cardiogenesis related transcriptional regulation and signaling pathways, an important strategy is to modulate the pathological microenvironment associated with heart injury, including inflammation, pro-fibrotic signaling pathways, and the mechanical properties of the damaged myocardium. We are optimistic that cardiac reprogramming will provide a powerful therapy in heart regenerative medicine.